Strategic Development Model for The Local Wisdom Based Small and Medium Enterprise (SMEs) : Using Analytical Hierarchy Process Ap-proach - Sucihatiningsih Dian Wisika Prajanti; Dalila Daud; Christina Litaay; Talitha Widiatningrum; Dhea Rizky Amelia (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2023)
The objective of this research is to construct a strategic development model for the local wisdom based SMEs in Magelang City of Central Java. SMEs become business entities that are prospective, have a high resilience and hugely contribute to the economy. Various attempts have also been made by the government to optimize the development of SMEs, in this case to those in Magelang City, with all their strengths and potentials. The â€œMagelang Kelurahan Entrepreneurship Centerâ€ program or abbreviated as â€œMagelang Kerenâ€has become one of the attempts from the Magelang City Government to support the SMEs succession. The mapping, synchronization, and harmonization in the attempt on empowering the SMEs is really needed as the basis of the policy to make an accurate program. This research used the descriptive qualitative and quantitative approach. The approach used is the Analytical Hierarchy Process (AHP) with the help of Geographic Information System (GIS) data analysis, using the House Model Analysis and the Fishbone Diagram. The findings of the research formulated that the attempt in developing the SMEs in Magelang City can be focused on the three main aspects, government policy, human resources and also the institutional. In the attempt of developing those specifically, it can be described by separating it into three alternatives that are prioritized, motivating the SMEs actors to improve the longevity of the business, training in promotion and marketing by using the IT, general training and the ease of the access on the registration as well as the procurement of HKI optimally that are centralized, consistent and sustainable.